A new perspective of the forming of calcareous layers above oil sand through the analysis of paleo-environment. Issue 1 (September 2020) - Wu, Zhaohui; Liu, Xiantai; Du, Yushan; Wu, Yinghao; Yang, Lingzhi; Zhai, Linxiu; Wu, Jinxi; Lao, Haigang; Wu, Jinfeng; Wu, Yingxin; Guo, Jinhui; Liu, Xilei; et al.
Abstract: Lithology and architecture of alluvial fans can become too complicated, influenced by rapid deposition of sediments near the provenance. The paleo-environment of oil sand can be often better observed through drilling cores and well loggings, rather than outcrops and seismic attributes, for the outcrops are usually covered by modern deposition and not allowed to be exploited while seismic waves often cannot detect layers too shallow above 200m. Reservoirs are mostly buried at extremely shallow depths from 0 to 500m. Oil is mostly found within a mixture of oil sand and carbonates. The calcareous layer, which is steady and widespread with a thickness of 0.5∼2m, is found above the oil sand layer in all wells. The limestone above oil sand layer shows a significant change of facies and paleo-environment. Only sandstone with abundant oil can easily form the carbonates above oil sand, which means the calcareous content is a result of temp and pressure change at the edge of oil layers. As a vivid description, the calcareous content is similar to the environment of calculus, which also underwent a change of pressure&temp with a concentration of CO2 . These phenomena can also be observed in micro-level or use chemical reactions to explain why both calculus and calcareous can form after they underwent temp and pressure change accompanied with oil.